2017
DOI: 10.5114/pjp.2017.69691
|View full text |Cite
|
Sign up to set email alerts
|

The utility of glomerular C4d immunostaining in renal biopsies in patients with immunoglobulin A nephropathy. A clinicopathological study

Abstract: The course of IgA nephropathy (IgAN) is highly variable and ranges from a totally benign condition to end-stage renal disease in approximately one third of cases. The identification of new prognostic markers could provide insights into the pathogenesis of IgAN and unveil new therapeutic avenues. Glomerular deposition of C4d is a marker of activation of the lectin pathway of complement. It is thought that activation of the lectin pathway in IgAN is associated with more severe renal damage, and more severe histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
9
0
4
Order By: Relevance
“…MBL deposits, found in about 25–35% of patients, have been associated with higher proteinuria, lower eGFR, and more severe histopathological lesions (70, 75). Several retrospective studies have confirmed the deleterious prognostic impact of mesangial C4d deposition on renal survival (71, 76, 77). In those series, the prevalence of C4d positivity ranged from 21% in the pediatric cohort up to 38% in the adult Spanish cohort (71, 76, 77).…”
Section: Complement Proteins and Complement Fragments In Pathologymentioning
confidence: 91%
“…MBL deposits, found in about 25–35% of patients, have been associated with higher proteinuria, lower eGFR, and more severe histopathological lesions (70, 75). Several retrospective studies have confirmed the deleterious prognostic impact of mesangial C4d deposition on renal survival (71, 76, 77). In those series, the prevalence of C4d positivity ranged from 21% in the pediatric cohort up to 38% in the adult Spanish cohort (71, 76, 77).…”
Section: Complement Proteins and Complement Fragments In Pathologymentioning
confidence: 91%
“…The formation of immune complexes could activate the complement system which is composed of classic, alternative and lectin pathways. The activation of complement system in IgAN were initially demonstrated by the presence of complement component C3, C4d, and C5-9 in glomeruli in IgAN patients (8)(9)(10). In recent years, researchers started to explore which complement pathway mediates the Gd-IgA 1 /anti-glycan immune complex induced glomerular damage in IgAN patients.…”
Section: Introductionmentioning
confidence: 99%
“…IF is more sensitive for the demonstration of capillary staining (i.e., peritubular capillaries), 6 but a side-by-side comparison of the 2 methods showed no significant difference for glomerular staining 3, 7. Both methods have been successfully used in native kidney samples 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19…”
mentioning
confidence: 99%